1995
DOI: 10.1093/ajcp/104.2.150
|View full text |Cite
|
Sign up to set email alerts
|

ThinPrep Versus Conventional Smear Cytologic Preparations in the Analysis of Thyroid Fine-Needle Aspiration Specimens

Abstract: Paired fine-needle aspiration specimens were analyzed from 41 surgically resected thyroid nodules, to compare diagnostic accuracy, amount (absent, mild, moderate, or marked) and pattern (diffuse, droplets, or both) of colloid, nuclear detail (poor, satisfactory, or excellent) and cytoplasmic detail (intact or disrupted) in ThinPrep (TP) (Cytyc, Marlborough, MA) versus conventional smear (CS) cytologic preparations. The 41 surgical specimens included 25 colloid nodules, 6 papillary carcinomas, 4 follicular aden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
116
2
1

Year Published

1997
1997
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(124 citation statements)
references
References 0 publications
4
116
2
1
Order By: Relevance
“…In that investigation the use of ThinPrep alone was as effective as CS in decreasing both inadequate and indeterminate cases whereas the majority of problems occurred when LBC and CS were simultaneously adopted (split sample, see above) [9]. These problems accounted for a high rate of inadequate and false-negative diagnoses and were also reported in many studies published in different countries [10,11,12,13,14]. In series where the direct-to-vial method is used, and all of the cellular material is therefore submitted for cytologic analysis, the average cellularity is generally higher than with the split-sample method and the rates of inadequacy and false positivity decrease significantly [9,13,15,16].…”
Section: Introductionmentioning
confidence: 92%
“…In that investigation the use of ThinPrep alone was as effective as CS in decreasing both inadequate and indeterminate cases whereas the majority of problems occurred when LBC and CS were simultaneously adopted (split sample, see above) [9]. These problems accounted for a high rate of inadequate and false-negative diagnoses and were also reported in many studies published in different countries [10,11,12,13,14]. In series where the direct-to-vial method is used, and all of the cellular material is therefore submitted for cytologic analysis, the average cellularity is generally higher than with the split-sample method and the rates of inadequacy and false positivity decrease significantly [9,13,15,16].…”
Section: Introductionmentioning
confidence: 92%
“…The TP Processor is a slidepreparation device that prepares a monolayer of cells on a glass slide from cells collected in an alcohol-based preservative solution (CytoLyt, Cytyc). Several articles [14][15][16][17][18][19][20][21][22][23][24] and some brief reports [25][26][27] have addressed the utility of TP in the evaluation of nongynecologic cytology samples. However, only a few studies have addressed its usage regarding salivary gland FNAB (SGFNAB) prepared by TP.…”
Section: Objective: To Retrospectively Assess the Diagnostic Accuracymentioning
confidence: 99%
“…While some studies have suggested that TP might have diagnostic sensitivity improved over that of CP in both gynecologic cytology 28 and some nongynecologic samples (urine), 29 the majority of reviews have indicated similar diagnostic accuracy for TP versus CP in nongynecologic cytology specimens. [14][15][16][17][18][19][20][21][22][23][24][26][27][28] This study reviewed the cytomorphologic features of SGFNABs processed by TP. It aimed to: (1) compare the diagnostic accuracy, cytologic features and pitfalls of TP versus CP in SGFNABs, and (2) evaluate the reproducibility of the cytomorphologic criteria used in the evaluation of FNABs prepared by CP versus TP.…”
Section: Objective: To Retrospectively Assess the Diagnostic Accuracymentioning
confidence: 99%
“…This technique has been introduced to obtain thin-layer smears in cervical cytology. The excellent results in this field prompted a wider application to virtually all cytological branches, including thyroid FNAB (20)(21)(22)(23)(24)(25)(26)(27). The current investigation has been carried out to evaluate the effectiveness of a panel made up by HBME-1 and Galectin-3 on LBC in identifying two subsets of FN/AUS with low and high malignant risk that might be managed differently to achieve a reduction of inappropriate surgery.…”
Section: Introductionmentioning
confidence: 99%